Use of Growth Hormone in the IVF Treatment of Women With Poor Ovarian Reserve - Hart, Roger J. (Frontiers in Endocrinology, 2019)
Growth hormone (GH) has been used as an adjunct in the field of female infertility treatment for more than 25 years, although, apart from treating women with GH deficiency its role has not yet been clarified. Contributing to this lack of clarity is that several underpowered studies have been performed on women undergoing IVF treatment, with a previous ‘poor response’ to ovarian stimulation, which have suggested a favourable outcome. Meta-analysis of randomised controlled trials has demonstrated a benefit for the use of the adjunct growth hormone, in comparison to placebo; with reductions in the duration of ovarian stimulation required prior to oocyte retrieval, with a greater number of oocytes collected, and improvements in many of the early clinical parameters with the use of GH. However, no benefit of an increased chance of a live birth with the use of growth hormone for the ‘poor responding’ patient has been determined. Consequently the role of GH to treat a woman with a poor response to ovarian stimulation cannot be supported on the basis of the available evidence. However, the place for GH in the treatment of women undergoing IVF may yet still be determined, as it is also used, without firm evidence of benefit; for women with poor embryonic development, poor endometrial development and for women who do not conceive despite multiple embryo transfers (recurrent implantation failure).